The performance of a solar assisted heat pump water heating system - Hawlader, Mohammad Nurul Alam; Chou, S K; Ullah, M Z (Pergamon, 2001)
Analytical and experimental studies were performed on a solar assisted heat pump water heating system, where unglazed, flat plate solar collectors acted as an evaporator for the refrigerant R-134a. The system was designed and fabricated locally, and operated under meteorological conditions of Singapore. The results obtained from simulation are used for the optimum design of the system and enable determination of compressor work, solar fraction and auxiliary energy required for a particular application. To ensure proper matching between the collector/evaporator load and compressor capacity, a variable speed compressor was used. Due to high ambient temperature in Singapore, evaporator can be operated at a higher temperature, without exceeding the desired design pressure limit of the compressor, resulting in an improved thermal performance of the system. Results show that, when water temperature in the condenser tank increases with time, the condensing temperature, also, increases, and the corresponding COP and collector efficiency values decline. Average values of COP ranged from about 4 to 9 and solar collector efficiency was found to vary between 40% and 75% for water temperatures in the condenser tank varying between 30°C and 50°C. A simulation model has been developed to analyse the thermal performance of the system. A series of numerical experiments have been performed to identify important variables. These results are compared with experimental values and a good agreement between predicted and experimental results has been found. Results indicate that the performance of the system is influenced significantly by collector area, speed of the compressor, and solar irradiation. An economic analysis indicates a minimum payback period of about two years for the system.